A STUDY OF OPERATING CONDITIONS OF SOLID WASTE MANAGEMENT OF SUBDISTRICT ADMINISTRATION ORGANIZATIONS IN CHACHOENGSAO PROVINCE - Panmart, Maliwan; Jeamponk, Paiboon (Life Sciences and Environment Journal, 2020)
The aim of the research was to study the operating conditions in the management of solid waste management of 74 subdistrict administrative organizations in Chachoengsao province. Questionnaires were used as tools for data collection. Statistics used in data analysis were percentage (%), mean ( ), and standard deviation (S.D.) The results showed that 60 questionnaires (81.08%) were able to be collected. The data of the factors supporting the operation were found to be at a moderate level ( =2.76, S.D. = 1.02). The results of the analysis of the operational processes were at the moderated level ( =3.11, S.D. = 1.08). And from the data reporting through 20 questionnaires (27.02%), the amount of solid waste generated was 74.3 tons/day (27,120 tons/year). The solid waste managed at 51.3 tons/day (18,725 tons/year). The solid waste left with no management was 23.0 tons/day (8,394 tons/year).